PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL QUANTUM TEACHING DI SD NEGERI 033 HUTABARINGIN MANDAILING NATAL - Syafrilianto Syafrilianto; Mariam Nasution; Melda Juniati (FORUM PAEDAGOGIK, 2022)
This study aims to improve student learning outcomes through the application of the Quantum Teaching model in ecosystem subject matter in class V SD Negeri 033 Hutabaringin. This research was carried out through the provision of actions with stages, namely planning, action, observation, and reflection. Subjects of this study were 28 students at SD Negeri 033 Hutabaringin Mandailing Natal. The research data was collected through multiple-choice item test instruments. Observation sheets and documentation were used to collect data on student and teacher activities. Data from the research results of the first cycle 1st meeting obtained students completed, 13 students (46.42%) and incomplete 15 students (53.58%) with an average (68.92). Furthermore, in the first cycle of the second meeting, 18 students were declared complete (64.29%), and 10 students were incomplete (35.71%) with an average (of 70.71). In the second cycle of the 1st meeting, 22 students completed (78.58%) and 6 students (21.42%) incomplete and average (75), while the second cycle of the 2nd meeting completed 24 students. Students (85.71%) and incomplete 4 students (14.29%) with average (80). It is concluded that the use of the Quantum Teaching model can improve student learning outcomes in SD Negeri 033 Hutabaringin Mandailing NatalÂ